Global Climate Policies, Local Institutions and Food Security in a Pastoral Society in Ethiopia - Virtanen, Pekka; Palmujoki, Eero; Gemechu, Dereje Terefe (Consilience, 2011)
This paper explores climate change adaptation within national policy priorities in a least developed country (LDC). The premise of the article is that when considering food security, climate is an exogenous trigger, while the deeper causes lie in social problems. Therefore, adaptation is subordinate to poverty alleviation. The paper examines how these two goals, climate adaptation and poverty alleviation, can be combined. Recent studies have shown that the most effective way to adapt to changing climate conditions in a poor country is to rely on local institutions that have established and sustainable mechanisms to deal with extreme climatic conditions. This research analyzes the stakeholder model, which calls for the participation of both governmental and non-governmental institutions, and how it is applied to climate change adaptation activities in Ethiopia. The study includes field research to analyze how local institutions are used to strengthen the resilience of communities in changing climate conditions. This research was carried out among pastoral communities in the Borana Zone and in the lowland areas of the Guji Zone in the Oromia Regional State of Ethiopia. The central methods of the study are semi-structured interviews with key stakeholders as well as secondary materials in the form of of policy statements, project documents and research literature. Theis research concludes that local institutions are poorly integrated into the process, while traditional adaptation strategies such as mobility are practically neglected.